Old Believers in Lithuania (1918–1940): Their Legal Status, Social Position and Emigration - Владимирович Поташенко, Григорий (Slavistica Vilnensis, 2009)
The article examines the legal status and social position of the Pomorian Old Believers in the Lithuanian Republic in 1918–1940 as well as their emigration abroad. In 1922, the Constitution of Lithuania set forth the principles of the relations between the State and the Church, which, in fact, were preserved throughout the period of the country’s independence. Оn Мау 20, 1923, the government issued the “Provisional Regulations concerning the Relationship between the Organization of the Old Believers of Lithuania and the Lithuanian Government”, whereby the autonomy of the Old Believers’ Church was recognized.In 1923, there were 32,149 Old Believers in Lithuania, which amounts 1,59% of the population. There were 53 active parishes with 51 spiritual fathers. The Old Believers of Lithuania constituted аn insignificant and relatively dispersed religious minority. In 1923, most Old Believers lived in villages (29,3–29,7 thousand people, or 91,1–92,4%), mainly in the north-eastern and central part of Lithuania. 2,4–2,8 thousand of Old Believers (7,6–8,9%) lived in cities and townships. In 1923–1924, an overwhelming majority of the Old Believers consisted of small farmers, а narrow layer of agricultural workers and tradesmen, as well as bу а relatively new, and small layer of middle-sized and large rural owners who were oriented toward market production.In 1923–1939, the total number of Russian emigrants from Lithuania amounted to 3-3,5 thousand people, which constituted 4–6% of the Russian population in Lithuania in 1930. The number of Old Believers among Russian emigrants amounts to no less than half of those leaving, i.e. 1,5–2,0 thousand people.